Restoration of NF-κB Activation by Tumor Necrosis Factor Alpha Receptor Complex-Targeted MEKK3 in Receptor-Interacting Protein-Deficient Cells - Blonska, Marzenna (American Society for Microbiology, 2004)
Receptor-interacting protein (RIP) plays a critical role in tumor necrosis factor alpha (TNF-α)-induced NF-κB activation. However, the mechanism by which RIP mediates TNF-α-induced signal transduction is not fully understood. In this study, we reconstituted RIP-deficient Jurkat T cells with a fusion protein composed of full-length MEKK3 and the death domain of RIP (MEKK3-DD). In these cells, MEKK3-DD substitutes for RIP and directly associates with TRADD in TNF receptor complexes following TNF-α stimulation. We found that TNF-α-induced NF-κB activation was fully restored by MEKK3-DD in these cells. In contrast, expression of a fusion protein composed of NEMO, a component of the IκB kinase complex, and the death domain of RIP (NEMO-DD) cannot restore TNF-α-induced NF-κB activation in RIP-deficient cells. These results indicate that the role of RIP is to specifically recruit MEKK3 to the TNF-α receptor complex, whereas the forced recruitment of NEMO to the TNF-α receptor complex is insufficient for TNF-α-induced NF-κB activation. Although MEKK2 has a high degree of homology with MEKK3, MEKK2-DD, unlike MEKK3-DD, also fails to restore TNF-α-induced NF-κB activation in RIP-deficient cells, indicating that RIP-dependent recruitment of MEKK3 plays a specific role in TNF-α signaling.